Novel self-healing glass-like CexOY film on a Flash-PEO coated AZ31B Mg alloy - Merino, E. (2024)
The aim of this work is to develop a glass-like CexOy coating to seal the pores of a Flash-PEO coated AZ31B Mg alloy and simultaneously provide smart corrosion protection. The cerium sol was synthesized using cerium acetate as main precursor. SEM micrographs revealed that upon cerium sol deposition, the pores of the oxide coating were effectively sealed, resulting in a double-layer coating system and thereby in a big reservoir of cerium ions (Ce3+/Ce4+). The glassy character of the cerium coating, confirmed by X-Ray diffraction, implies that cerium exists in Ce3+ and Ce4+ ionic states enclosed in a high internal energy structure which facilitate the diffusion of cerium ions to active cathodic zone. Electrochemical Impedance Spectroscopy (EIS), X-Ray Diffraction (XRD), and Raman spectroscopy were used to explore the active corrosion protection of the CexOy cerium sol-gel coating. The corrosion inhibition mechanism involves the migration of cerium ions and the precipitation of insoluble-crystalline cerium compounds (CeO2). The coating demonstrated self-healing properties, presenting a promising alternative to traditional chrome conversion coatings (CCC).